Tingkat Kemampuan Pukulan Lob Bulutangkis Peserta Ekstrakulikuler Bulutangkis Di SMPN 1 Kotabaru Cikampek - Noviani Cahya Nur Asri; Bambang Ismaya; Ruslan Abdul Gani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This Research is Motivated by the Problem of not knowing level of badminton lob hitting ability of badminton extracurricular participants at SMPN 1 KOTABARU Cikampek Therefore. the purpose of this study was to determine the level of badminton lob hitting ability of badminton extracurricular participants at SMPN 1 KOTABARU Cikampek the Approach in this research is descriptive with a quantitative approach. The Method used is a survey method with test and measurement techniques. The Population used was all badminton extracurricular participants at SMPN 1 KOTABARU Cikampek as many as 15 students and the sample used was total sampling technique. The Level of badminton lob hitting ability of badminton extracurricular participants at SMPN 1 KOTABARU Cikampek based on the result of this study showed that in the Very Good category it was 13% (2 students), in the Good category it was 13% (2 Students), in the Enough category it was 40% (6 Students), in the Less category it was 0% (0 students), and in the Very Poor it was 33% (5 Students). It means, the highest level of badminton lob hitting ability of badminton Extracurricular Participants at SMPN 1 KOTABARU Cikampek is in the Enough Category or it can be said to be Enough..